From Grassroots to Growth: Strengthening Communities through Financial Support for SMEs - Rahmadi, Galih; Rozamuri, Arif Murti (Golden Ratio of Community Services and Dedication, 2024)
This research investigates the nexus between small business financing, community empowerment, and local prosperity. Employing a qualitative descriptive methodology, the study systematically reviews and synthesizes existing literature from diverse sources, including academic journals, books, reports, and online databases. Thematic analysis is utilized to identify recurring themes, patterns, and insights relevant to the research domain. The findings highlight the pivotal role of small businesses as engines of economic growth, social cohesion, and environmental stewardship within local communities. Access to finance emerges as a critical determinant of entrepreneurial success and community development, with innovative financing mechanisms such as microfinance and impact investing playing a significant role in addressing the financing gap and promoting inclusive growth strategies. Moreover, the study underscores the interconnectedness of economic, social, and environmental factors in shaping SME development and its broader implications for community well-being. The research contributes to theoretical understanding by offering a multidimensional perspective on small business financing and community empowerment, while also providing actionable insights for policymakers, practitioners, and entrepreneurs seeking to leverage financial resources for inclusive and sustainable development.